Социальная мотивация: проблемы и решения - Москвичев, С. (Социология: теория, методы, маркетинг, 2004)
Among problems of social and psychological theory, the social motivation one is still
unelaborated. Idea of the origin of social incentives is ambiguous. Social motivation is
regarded in the background of “organic trend” and “personal reductionism”. Socioe-thnic processes, as well as group phenomena, were proved to affect social behavior.
The author discusses interpersonal relations influencing the social motivation. There
are determined four motivation mechanisms of interaction between individuals that
depend on each other. It is stressed that measuring of social incentives and determination of their place in the general motivational structure are very important. As a
result, the author compiled an opened catalog of human social needs.